Entrepreneurship teaching: A study about best practices and antecedents of Brazilian teachers - Ribeiro, Artur Tavares Vilas Boas; Ferragi, Cesar Alves; Zanotto, Maria Angelica do Carmo; Cardoso, André Coimbra Felix (REGEPE Entrepreneurship and Small Business Journal, 2022)
Objective: to know concrete practices of teaching entrepreneurship, as well as the professional/academic background of teachers, in order to fill gaps observed in the literature on the subject. Method: data collection of entrepreneurship teachers recognized for their classroom practice (selected by the snowball procedure), through 10 semi-structured and in-depth interviews, examined by the content analysis technique. Results: identification of 30 best practices, categorized according to their emphases and respective bases, highlighted here in parentheses. They are: (a) learning (projects), (b) learning (problems), (c) reflective exercises, (d) expository (cases), (e) expository (invited entrepreneurs), and (f) expository (debates and quizzes). After detailing the activities, findings about the teachers’ background were presented, in a complementary way, such as entrepreneurial experience, professional and international experiences, corroborating the existing literature on the subject. Theoretical/methodological contributions: by presenting boundaries, in terms of classroom approaches, the best practices contribute to the literature, as they strengthen the arguments in favor of experiential models, as well as project-based or problem-based learning. In addition, the results confirm what the literature points out in relation to the antecedents of entrepreneurship teachers. Originality/Relevance: this study deepens the understanding of best practices in entrepreneurship education, something previously mentioned as superficial and generic (Gedeon, 2014). Social/managerial contributions: the results allow entrepreneurship teachers to replicate best practices within their educational settings, as the paper provides a wide range of detailed pedagogical practices that they might employ. JEL Code: L23, I23, I28 e I25